Kebijakan Optimalisasi Peran Badan Usaha Milik Daerah (BUMD) Jawa Timur - Dwi Budi Santosa (Jurnal Aplikasi Manajemen, 2011)
State enterprises in regional level (BUMD) are accepted as inefficient enterprises,especially becoming burden fiscal. Therefore, this paper providesbackground research for potential policies to optimize the role of BUMD in dealing to regional economic development in East Java and discuses (i) the role of BUMD in an economic activities, and (ii) BUMD performance. Based on the result, all BUMD owned by Provincial Government show operating in low level of efficiency. This result has two main implication: (i) associated with public goods, consumers should pay expensive compensation to get public goods, (ii) BUMD appear still not effective to influence market fluctuation. There are two suggestions to optimize the role of BUMD. First, BUMD should improve the management to increase economic of scale. Second, BUMD in non-strategist sector can be sold to avoid an increases fiscal gap.Keywords: BUMD, BCG, Strategic Management